The dynamics of MILO (Multimedia Interactive Learning Online) in role playing: enhancing the learning process in COVID-19 pandemic / Woo Pak Yuan ... [et al.] - Woo, Pak Yuan; Isa, Nina Farisha; Azmi, Ezwani (2021)
The onset of COVID-19 pandemic has affected the learning process of students throughout Malaysia, especially university students. A paradigm shift is needed in making the learning more dynamic was proposed in this research paper through the lenses of Multimedia Interactive Learning Online (MILO). This software was to enhanced and strengthened role playing among university students enrolling hospitality Front Office course. Similarly, role playing can act as a transition point from classroom into the hospitality industry, vis-ǎ-vis to an extremely complex operating environment. Consequently, a well practice role playing in the absence of face to face learning supervision, may help students to gain a high degree of motivation and subsequently confidence into executing relative tasks at ease in any given time and situations. To this end, role playing is an extremely vital component for students to be successful both in classroom and in the hospitality industry.